Iba Si Eba: An Assessment of the Gender and Development (GAD) Program as a Basis for Improvement - Brosas, Kaisser A; Asoy, Hazel Ann C.; Peligrina, Hermervash C.; Villa, Elizabeth B. (Future Science / FSH-PH Publications, 2025)
This study assessed the Gender and Development (GAD) program in Lucena City, with the objective of assessing community awareness, availability of the program, participation, existing policies, and barriers to implementation. A descriptive quantitative research design and purposive sampling were used to gather data from five barangays with the largest populations. Findings were supposed to inform the development of integrated and sustainable GAD initiatives addressing gender-based violence and promoting gender equality effectively. Demographics reflect participatory involvement from the younger generations, who are mostly within the 18-27 age category. Women are very participatory at 78%; hence, there needs to be a participatory balance between men and LGBTQIA+ sectors. 39% were college-educated, but this did not transfer to high levels of awareness as information and outreach were not dispersed. The programs were not made available to all barangays; scheduling, access, and resources were all different and not accessible at the same levels to participate. Yet, staff training, resource allocation, community involvement, and policy implementation still face issues. Recommendations would include diversification in communication strategy, inclusiveness, program inconsistencies, and monitoring and implementation mechanisms. This study, therefore, served to highlight the importance of partnership between local governments, stakeholders, and community people in the enhancement of gender equality and the effectiveness of GBV, leading to safer communities.